The effects of Turkish accession to the EC on population and the labour market - Elmar Hönekopp (Intereconomics, 1993)
Demography and the labour market are two important aspects that will have to be discussed in connection with possible Turkish membership of the European Community. The following article discusses these aspects primarily with regard to the situation in the EC and in Germany, which in the past was the main host country for Turkish migrants and will probably continue to be so in the future.
Keywords: 330; EC